Sistem Informasi Pemerintah Daerah Pada Badan Keuangan Dan Aset Daerah Kota Bitung; Implementasi, Kendala dan Solusi - Banea, Agnes Eyne (Jurnal Ilmiah Akuntansi Peradaban, 2024)
One important tool for local government modernization is the Local Government Information System (SIPD). If implemented correctly, SIPD can improve the efficiency, transparency and quality of public services and aid decision-making. However, the successful implementation of SIPD relies heavily on adequate infrastructure, human resource training, budget support, and supportive policies. The purpose of this research is to find out how the implementation of SIPD at BPKAD Bitung City, the obstacles faced and solutions to overcome the obstacles to SIPD implementation. This research is a qualitative research with an explorative approach. The research data was collected through interviews and literature study. Furthermore, the data was analyzed using content analysis. The results showed that the implementation of SIPD at BPKAD Bitung City has been in accordance with Permendagri Number 70 of 2019 concerning Regional Government Information Systems and based on the theoretical aspects of implementation has been successful. The obstacles in the implementation of SIPD at BPKAD Bitung City include unstable internet connection and delayed response from the Ministry of Home Affairs.